Peran Pembelajaran Pendidikan Pancasila Melalui Habit of Mind Menyanyikan Lagu Indonesia Raya Untuk Meningkatkan Nasionalisme Peserta Didik (Studi Kasus di Kelas VIII SMP Pasundan 3 Bandung) - Pupung Lestari; Cahyono Cahyono; Asep Deni Normansyah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The decline of students' nationalism due to globalization and rapid technological development has become a challenge in Pancasila Education. One effort to address this issue is through the Habit of Mind of singing the Indonesian national anthem, Indonesia Raya, before the learning process begins. This study aims to analyze the role of Pancasila Education through the Habit of Mind of singing Indonesia Raya in improving the nationalism of eighth-grade students at SMP Pasundan 3 Bandung. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the habituation of singing Indonesia Raya contributes to improving students' discipline, patriotism, respect for national symbols, responsibility, and pride as Indonesian citizens. Although challenges remain, including students' low awareness and environmental influences, teachers address them through role modeling, habituation, and continuous motivation. Therefore, Pancasila Education through the Habit of Mind of singing Indonesia Raya contributes to strengthening students' nationalism.